Evidence-Based Studies and Perspectives of the Use of Brazilian Green and Red Propolis in Dentistry - Carvalho, Claudemir de; Fernandes, Wesley Henrique Cabral; Mouttinho, Thays Barreto Freitas; Souza, Daniela Martins de; Marcucci, Maria Cristina; D’Alpino, Paulo Henrique Perlatti (European Journal of Dentistry, 2019)
This review analyzes the evidence and perspectives of dental use of the green and red propolis produced in Brazil by Apis mellifera L. Multiple applications of propolis were found considering its antibacterial, antifungal, anti-inflammatory, immunomodulatory, antiviral, and healing properties. Its therapeutic effects are mainly due to the presence of alcohols, aldehydes, aliphatic acids, aliphatic esters, amino acids, aromatic acids, aromatic esters, flavonoids, hydrocarbyl esters, ethers, fatty acids, ketones, terpenes, steroids, and sugars. Propolis has been mainly used in dentistry in the composition of dentifrices and mouthwashes. Studies have also demonstrated promising use against dentin hypersensitivity, root canal treatment, Candida albicans, and other microorganisms. Overall review of the literature presented here demonstrated that both Brazilian green and red propolis are effective for the problems of multiple etiologies that affect the oral cavity in different dental specialties.
Keywords: green propolis; red propolis; antibacterial activity; natural products